(untitled) (Muitas Vozes, 2021)
This text deals with the work A paixão segundo G.H. from Clarice Lispector, taking it from a work of literary writing thought as an operation of production of the sensitive in existence. A work that, more than producing meanings or generating interpretations that would help us to understand the world, make worlds, produce their own forms, capable of attributing different configurations to existence and its thinking. In the case of Lispector’s work, this process occurs, not through the construction of any new world, but from the overthrow of the definitions and purposes of this world, the possibility of which is manifested in the meeting between G.H. and the cockroach. Such a relationship, then, operates a strife not only of G.H. with the animal, but the questioning of the existence of humanity, insofar as it becomes a paradigm of this relationship. For this purpose, we operate through four registers, showing as a result the procedure of this possibility: collapse, open, becoming and inform, starting from authors as Giorgio Agamben, Gilles Deleuze and Felix Gauttari and Georges Bataille. More than a stop from the possibility of understanding humanity in G.H., we are faced with a deeply displaced retoritorializing machine, out of the human and out of direction.